Evaluation of face shields used during aerosol generating procedures - Alessandra A. Pratt; Grant D. Brown; Jarrett E. Walsh; Henry T. Hoffman; Matthew W. Nonnenmann (Scientific Reports, 2023)
Abstract Transnasal flexible laryngoscopy is considered an aerosol generating procedure. A negative pressure face shield (NPFS) was developed to control aerosol from the patient during laryngoscopy. The purpose of this study was to determine the effectiveness of the NPFS at controlling virus aerosol compared to a standard disposable plastic face shield. The face shields were placed on a simulated patient coughing machine. MS2 bacteriophage was used as a surrogate for SARS-CoV-2 and was aerosolized using the coughing machine. The aerosolized virus was sampled on the inside and outside of the face shields. The virus aerosol concentration was not significantly different between the inside and outside of the traditional plastic face shield (p = 0.12). However, the particle concentrations across all particle sizes measured were significantly decreased outside the face shield. The virus and particle concentrations were significantly decreased (p < 0.01) outside the NPFS operating at a flow rate of 38.6 L per minute (LPM). When the NPFS was operated at 10 LPM, virus concentrations were not significantly different (p = 0.09) across the face shield. However, the number particle concentrations across all particle sizes measured were significantly different (p < 0.05).